Torta de girassol na dieta de cordeiros confinados - Rodrigues, Deivison Novaes (2012)
Two experiments were conducted simultaneously in the sector of Sheep Experimental Farm of Federal University of Mato Grosso, with the objective to evaluate the nutritional parameters, performance and costs of production, of sheep feedlot and subjected to levels of 0%, 7%, 14%, 21% and 28% inclusion of sunflower cake in total dry matter of diet. In experiment 1, it was evaluated the effects of inclusion of sunflower cake on intake and digestibility of nutrients, pH and rumen ammonia nitrogen, as well as blood glucose concentration. Five crossbred , castrated and woolless sheep, with initial body weight of 65.59 ± 6.53 kg were used by a 5 x 5 latin square design. The experiment lasted 60 days divided into five periods of 12 days each, the initial 7 days for animal adaptation and 5 final days to the evaluations (intake and digestibility of nutrients, pH and rumen ammonia nitrogen, and the blood glucose concentration). The sheep were maintained in individual cage, which permitted the control of food supplied and orts for the intake determination. The indigestible NDF was used as a marker to estimate the feces excrection. The inclusion of sunflower cake did not influence (P>0.05) the daily intake of dry matter (DM), organic matter (OM), crude protein (CP) and neutral detergent fiber (NDF),it has been observed mean values of 1.25 kg, 1.15 kg, 179.10 g and 400.71 g, respectively. For the DM, OM, CP and NDF digestibility, the sunflower cake did not promote effect (P>0.05), it has been observed means of 63.9, 66.0, 60.9 and 33.1%, respectively. The blood glucose levels were decreased in 0.1156 mg/dL for each 1% of sunflower cake included in the diets, while for the time effect after the intake, it was estimated the higher level of 64.56 mg/dL ,being observed 2.57 h after feeding The rumen pH was linearly increased in 0.0105 units for each 1% of sunflower added to diets, while the minimum rumen pH (5.63) was estimated 5.14 hours after feeding. The minimum rumen ammonia concentration (9.75 mg/dL) was verified with addition of 19.34% of sunflower cake. In experiment 2, it was evaluated the effects of inclusion of sunflower cake on the animal performance, daily dry matter intake, feed conversion and productions costs. Forty crossbreed lambs, not castrated, with average initial body weight 20.17 ± 2.66 kg, using a randomized block design. The experiment lasted 70 days, the 14 initial days designated to animals adaptation and final 56 days to animal evaluation (performance, daily dry matter intake, feed conversion and productions costs). The different levels of inclusion of sunflower cake in the diets of feedlot sheep did not affect (P>0.05) DM intake (g/day and % of body weight) and feed conversion, it has been observed average values of 883.58 g, 3.41% e 4.40, respectively. It has not been observed effects (P>0.05) of sunflower cake levels on water intake (L/day and L/kg of dry matter), it has been observed average values of 2.59 L and 2.94 L/kg, respectively. However, the sunflower cake levels promoted a linear decrease (P≤0.05) on final body weight (kg), total body weight gain (kg), average daily gain (g) and loin eye area (cm2). The costs referent to the diets decreased with the inclusion of sunflower cake, however only the revenue daily gross of treatment with 14% inclusion showed itself equal to treatment with 0% inclusion. It was concluded that the sunflower cake can be added up to 28% in the diet of sheep without affect the intake, rumen environment and digestion, however, to obtain a reduced cost under the weight body gain of feedlot lambs, the sunflower cake can be added up to 28% of DM, its price can represent up to 40% of the cost of the blend of corn and soybean meal, and up to 21% of DM, when its price represents from 40% to 72% of the blend of corn and soybean meal.